Rapid Screening of Volatile Organic Compounds from Aframomum danielli Seeds Using Headspace Solid Phase Microextraction Coupled to Gas Chromatography Mass Spectrometry - Mosotho J. George; Patrick B. Njobeh; Sefater Gbashi; Gabriel O. Adegoke; Ian A. Dubery; Ntakadzeni E. Madala (International Journal of Analytical Chemistry)
Volatile organic compounds (VOCs) derived from plants have been used in the fragrance industry since time immemorial. Herein we report on the rapid screening of VOCs from seeds of ripe Aframomum danielli (family, Zingiberaceae) using a polydimethylsiloxane fibre headspace solid phase microextraction coupled to a gas chromatography mass spectrometry (SPME-GC/MS) instrument. Portions of 0.25, 0.35, and 0.50 g of ground sample were weighed and extraction of volatile organic compounds (VOCs) was achieved using a 100 μm polydimethylsiloxane solid phase microextraction (PDMS SPME) fibre, with the equilibrium time of 40 minutes and extraction temperature of 50°C; the following compounds with their respective relative abundances were obtained as the top ten most abundant and annotated ones using NIST, Wiley, and Fragrances Libraries: eucalyptol (58%); β-pinene (22%); α-pinene (7.5%); α-terpineol (4%), α-terpinyl acetate (2%); α-bergamotene (1%); pinocarveol (0.39%); α-copaene (0.35%); caryophyllene (0.34); and β-bisabolene (0.31%). These compounds have been reported elsewhere in the literature and listed in the Fragrances Library, incorporated into the Saturn QP2020 GCMS Solution® software used for their analysis.